2012
DOI: 10.2337/db11-1494
|View full text |Cite
|
Sign up to set email alerts
|

Novel Role of the IGF-1 Receptor in Endothelial Function and Repair

Abstract: We recently demonstrated that reducing IGF-1 receptor (IGF-1R) numbers in the endothelium enhances nitric oxide (NO) bioavailability and endothelial cell insulin sensitivity. In the present report, we aimed to examine the effect of increasing IGF-1R on endothelial cell function and repair. To examine the effect of increasing IGF-1R in the endothelium, we generated mice overexpressing human IGF-1R in the endothelium (human IGF-1R endothelium-overexpressing mice [hIGFREO]) under direction of the Tie2 promoter en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 38 publications
2
47
0
Order By: Relevance
“…Signal cascades induced by IGF-1 mediate many cellular responses, including proliferation, differentiation, and angiogenesis (8, 33), and are also involved in tumor angiogenesis and developmental neovascularization in human and zebrafish (12,13,34). A recent study demonstrated that IGF-1R activation by IGF-1 promotes differentiation of stem cells into mesoderm and endothelial progenitor cells into mature ECs, indicating IGF-1 as a potential drug for enabling vascular regeneration (12).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Signal cascades induced by IGF-1 mediate many cellular responses, including proliferation, differentiation, and angiogenesis (8, 33), and are also involved in tumor angiogenesis and developmental neovascularization in human and zebrafish (12,13,34). A recent study demonstrated that IGF-1R activation by IGF-1 promotes differentiation of stem cells into mesoderm and endothelial progenitor cells into mature ECs, indicating IGF-1 as a potential drug for enabling vascular regeneration (12).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that IGF-1R activation by IGF-1 promotes differentiation of stem cells into mesoderm and endothelial progenitor cells into mature ECs, indicating IGF-1 as a potential drug for enabling vascular regeneration (12). Moreover, endothelium-targeted IGF-1R transgenic mice enhance endothelial remodeling and vasorelaxation (13), suggesting that an activator of IGF-1R may be a useful therapeutic strategy to treat vascular repair and hypertension disorders. In this study, we found that Rg5 activated common angiogenic signal pathways via IGF-1R.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, infusion of these cells into WT mice increased endothelial repair without altering atherosclerotic lesion formation. Overexpression of IGF1 receptors on endothelial cells increased hybrid formation and reduced NO bioavailability (Imrie et al 2012). However, perhaps surprisingly, endothelial regeneration was enhanced by IGF1 receptor overexpression after arterial denudation.…”
Section: Igfs and Atherosclerosismentioning
confidence: 95%
“…Insulin-stimulated NO synthesis in cultured endothelial cells is independent of Ca 2+ concentration but dependent on IRS1-PI3K-PDK1-Akt pathway activation [1,3,7]. IGF-1 has been reported to be a markedly less effective stimulus for NO synthesis -indeed, recent elegant studies using mice with an endothelial-specific knockdown of IGFR or overexpression of IGFR have reported that the IGFR is a negative regulator of insulin-stimulated NO synthesis, perhaps due to formation of IR-IGFR heterodimers that are less sensitive to insulin than IR homodimers [22,23]. eNOS is subject to reversible phosphorylation at several sites [24], and Akt-mediated phosphorylation of eNOS at Ser1177, which reduces the requirement for Ca 2+ and permits NO synthesis in the absence of increased cellular Ca 2+ is required for insulin-stimulated NO synthesis in cultured endothelial cells ( Figure 2) [7,24].…”
Section: Insulin Stimulation Of Endothelial No Synthesismentioning
confidence: 99%